Accelerated aging test for forage pea seeds - Machado, Carla Gomes; da Silva, Givanildo Zildo; de Oliveira, Silvia Sanielle Costa; Martins, Cibele Chalita [UNESP] (Universidade Estadual de Londrina, 2019)
Forage pea is an important annual, cold climate crop with high levels of essential amino acids in its seeds, which are lacking in the composition of cereal grains. Therefore, livestock farmers use its seeds as a nutritious source of forage. To plant fields of this forage, it is necessary to know the quality of the seeds, determined through germination and vigor tests. In the literature, studies on vigor tests for forage pea seeds are scarce. This study aimed to verify the efficiency of vigor tests, with emphasis on accelerated aging to evaluate the physiological quality of forage pea seeds in order to select lots for seedling emergence in the field. Using accelerated aging tests, 10 lots of forage pea were evaluated for moisture content, thousand-seed weight, emergence percentage, emergence first count, speed index of seedlings in the field, germination, germination first count, and electrical conductivity. The following variations of methodology were used: temperatures of 41 and 42 °C, exposure times of 48 and 72 h, and different relative humidity values in the aging atmosphere, using distilled water (100 % RH), saturated solution of potassium chloride (87 % RH), and sodium chloride (76 % RH). The tests of germination, emergence first count of seedlings in the field, emergence speed index, and electrical conductivity are promising to evaluate the vigor of forage pea seed lots. The accelerated aging test conducted in a solution saturated with potassium chloride at 42 °C for 48 h is adequate to estimate the vigor of forage pea seed lots, providing information similar to that of the emergence of seedlings in the field.
Keywords: Arvense; Deterioration; Pisum sativum subsp; Vigor